Simultaneous realization of high catalytic activity and stability for catalytic cracking of n-heptane on highly exposed (010) crystal planes of nanosheet ZSM-5 zeolite. Issue 65 (26th July 2016) - Xiao, Xia; Zhang, Yaoyuan; Jiang, Guiyuan; Liu, Jia; Han, Shanlei; Zhao, Zhen; Wang, Ruipu; Li, Cong; Xu, Chunming; Duan, Aijun; Wang, Yajun; Liu, Jian; et al.
Abstract : Nanosheet ZSM-5 zeolite exhibits outstanding reactivity and anti-coking stability for catalytic cracking of n -heptane. Abstract : Nanosheet ZSM-5 zeolite with highly exposed (010) crystal planes demonstrates high reactivity and good anti-coking stability for the catalytic cracking of n -heptane, which is attributed to the synergy of high external surface area and acid sites, fully accessible channel intersection acid sites, and hierarchical porosity caused by the unique morphology.